2021
DOI: 10.1080/0886022x.2021.1871920
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of predialysis patients’ symptoms in peritoneal dialysis patients

Abstract: Background As kidney disease progresses, patients often experience a variety of symptoms. There are very few studies reporting spectrum of predialysis patients’ symptoms in peritoneal dialysis (PD) patients. Furthermore, the clinical significance of predialysis patients’ symptoms for PD patients’ prognosis remains unknown. Methods In this retrospective cohort study, patients who started PD during 1 January 2006 to 31 January 2018 were included. Patients’ predialysis sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The association of sleep quality with outcomes is likely to be observed among exclusively PD patients; however, there is a paucity of data in this respect. In a recent study, among the symptoms (including anorexia, insomnia, fatigue, and nausea) experienced by patients undergoing PD, only nausea showed a significant association with all-cause mortality despite a high prevalence of insomnia (32.7%) in PD patients [ 33 ]. Then, we also investigated for the first time the association of HRQOL sleep score with HD transfer, which is an important outcome for PD patients in addition to death.…”
Section: Discussionmentioning
confidence: 99%
“…The association of sleep quality with outcomes is likely to be observed among exclusively PD patients; however, there is a paucity of data in this respect. In a recent study, among the symptoms (including anorexia, insomnia, fatigue, and nausea) experienced by patients undergoing PD, only nausea showed a significant association with all-cause mortality despite a high prevalence of insomnia (32.7%) in PD patients [ 33 ]. Then, we also investigated for the first time the association of HRQOL sleep score with HD transfer, which is an important outcome for PD patients in addition to death.…”
Section: Discussionmentioning
confidence: 99%
“…[46,49] Finally, predialysis symptoms may also be predictors of prognosis on PD; in a study of over 800 incident PD patients, nausea and anorexia were found to be associated with short-and long-term mortality on PD. [51] Together, these studies highlight the importance of recognizing how high symptom burden in PD patients may not only affect health-related outcomes, but also reflect subjective patient perception of disease and consequently, dialysis-related decision-making.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“… 45 , 48 Finally, predialysis symptoms may also be predictors of prognosis with PD; in a study of over 800 incident PD patients, nausea and anorexia were found to be associated with short- and long-term mortality with PD. 49 …”
Section: Symptom Burden and Hrqol In Patients Receiving Pdmentioning
confidence: 99%
“…21(5):493–499 https://doi.org/10.1111/1744-9987.12546 [ 15 ] Older age (≥ 65 years) Albumin (≤ 3.5 g/dL) Overweight/obesity Hypocalcemia before PD start (≤ 8.4 mg/dL) Heart failure (41%) Peritonitis (22%) Inadequate dialysis dose (10%) Malignancy requiring surgery (10%) 17% (27/158) transfer to HD e 8.9% (14/158) combination use of HD e 5.7% (9/158) death from any cause e Prognostic implications of predialysis patients’ symptoms in peritoneal dialysis patients (2021) Renal Failure. 43(1):216–222 https://doi.org/10.1080/0886022X.2021.1871920 [ 23 ] Nausea (all-cause mortality) Anorexia (long-term mortality) 3.1% (28/898) transfer to HD 42.8% (384/898) death Early discontinuation Adapted from: Time-dependent reasons for peritoneal dialysis technique failure and mortality (2010) Perit Dial Int. 30:170–177 https://doi.org/10.3747/pdi.2008.00277 [ 8 ] Loss of residual renal function a Older age a Diabetes, CV disease a Female a Death (about 25%) a Psychosocial/unknown (about 20%) a Catheter complications (15%) a Transplantation (13%) a Infections (about 10%) a Under dialysis/UFF/abdominal complications (about 17%) a 13% (during the first year) Early failure in patients starting peritoneal dialysis: a competing risks approach (2014) Nephrol Dial Transplant.…”
Section: Early Vs Late Pd Discontinuation Definitionmentioning
confidence: 99%
“…In this context, the Patient Reported Outcome Measures (PROMs) have shown some promise in predicting dialysis discontinuation [ 22 ]. A recent Chinese study [ 23 ] sought to investigate whether pre-dialysis symptoms are linked to mortality in patients on PD treatment. The authors used data of 898 patients (excluding patients who received HD for more than one month before PD start and those who had a kidney transplantation), and they observed that nausea was associated with all-cause mortality after 6 and 12 months from PD start while anorexia was the only symptom significantly associated with long-term mortality, after adjusting for confounding factors.…”
Section: Early Vs Late Pd Discontinuation Definitionmentioning
confidence: 99%